2020
DOI: 10.1016/j.neuroimage.2019.116372
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric development of the human fetal cerebellum during the early second trimester

Abstract: The protracted nature of development makes the cerebellum vulnerable to a broad spectrum of pathologic conditions, especially during the early fetal period. This study aims to characterize normal cerebellar growth in human fetuses during the early second trimester. We manually segmented the fetal cerebellum using 7.0-T high-resolution MR images obtained in 35 specimens with gestational ages ranging from 15 to 22 weeks. Volume measurements and shape analysis were performed to quantitatively evaluate global and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Shape analysis, on the other hand, has been performed to observe the local changes of brain regions in diverse communities ( Lai et al, 2009 ; Shi et al, 2011 ; Tae et al, 2011 ; Ng et al, 2014 ; Gahm and Shi, 2016 ). Similar research was proposed in previous publications on the development of fetal brain regions including the HF and cerebellum ( Ge et al, 2015 ; Xu et al, 2020 ). As to the blind hippocampi, relevant results demonstrated that the anterior part of the right HF is larger with blind individuals compared to the sighted controls based on shape analysis method ( Leporé et al, 2009 ).…”
Section: Introductionsupporting
confidence: 85%
“…Shape analysis, on the other hand, has been performed to observe the local changes of brain regions in diverse communities ( Lai et al, 2009 ; Shi et al, 2011 ; Tae et al, 2011 ; Ng et al, 2014 ; Gahm and Shi, 2016 ). Similar research was proposed in previous publications on the development of fetal brain regions including the HF and cerebellum ( Ge et al, 2015 ; Xu et al, 2020 ). As to the blind hippocampi, relevant results demonstrated that the anterior part of the right HF is larger with blind individuals compared to the sighted controls based on shape analysis method ( Leporé et al, 2009 ).…”
Section: Introductionsupporting
confidence: 85%
“…We found an abnormal cerebellar morphometry in fetuses of women with PCOS, as indicated by smaller VH and larger APDV of cerebellum. Although we failed to get the growth pattern of cerebellum in fetuses of women with PCOS, the opposite trend of alterations in VH and APDV of cerebellum may be associated with the change in cerebellar functions, as the different growth rates of cerebellar subregions are related to their functional characteristics [ 20 ]. Furthermore, fetuses of women with PCOS presented increased HIA value after 32 gestational weeks, reflecting an abnormal hippocampal rotation process associated with hippocampal development or other cortical malformations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another s study to assess the fetal cerebellum, the relationship between the anterior-posterior diameter follows the first-order polynomial as the best fit predictive equation(Chang et al 2000b) which was similar to our study. The similar study using 7T MRI scan among forty (40) Chinese fetuses, they found the correlation between the cerebellar volume the gestational age follows the second order polynomial curve in the second trimester of pregnancy (14-22) weeks of gestation(Liu et al 2011), and another study in the same Chinese fetuses with the sample size of thirty five(35) fetuses from 15-22 weeks of gestation which shows the cerebellar volume increases by following the second- order polynomial(Xu et al 2020),in this study, however, we used the large sample size 144 fetuses and we included the fetuses from second and third trimester of pregnancy, 18-37 weeks of gestation, we also included the 25 th ,50 th ,75 th for each gestational age, we showed the sex differences in cerebellar volume, superior-inferior and anterior-posterior diameters.…”
Section: Discussionmentioning
confidence: 98%